A Comment on the Appellate Body Report in EC‐Seal Products in the Context of the Trade and Environment Debate. Issue 3 (18th November 2014) - Marceau, Gabrielle
<x xml:space="preserve">Abstract</x> The Appellate Body (AB) Report in EC‐Seal Products has potential ramifications for the environmental or social concerns in the World Trade Organization. It refines the jurisprudence on the balance between members' market access obligations and their right to give priority consideration to non‐trade concerns under the General Agreement on Tariffs and Trade (GATT) and the Agreement on Technical Barriers to Trade (TBT). This article outlines the main points of the AB Report, particularly related to what measures constitute technical regulations within the scope of the TBT Agreement, and the relationship between the GATT and TBT Agreement in the context of the pursuit of legitimate non‐trade concerns. It further highlights one of the issues raised in the report concerning processes and production methods (PPMs). In particular, it offers comments on what could constitute product‐related and non‐product related PPMs – a categorization that has emerged in the trade‐environment doctrine over the last 40 years and that should now be informed by the AB's interpretation of the TBT Agreement in this case.